ANALYSIS DETERMINANTS THE VELOCITY OF MONEY IN INDONESIA - Dewi Novitasari; Astuti, Ratna Fitri; Sutrisno, Sutrisno (Educational Studies: Conference Series, 2023)
This study aims to analyze the effect of gross domestic product, inflation, and interest rates on the velocity of money in Indonesia for the period 2011 quarter I to 2020 quarter IV. This type of research is descriptive research with a quantitative approach. Research data was obtained from publications by the Central Bureau of Statistics (BPS) and Bank Indonesia. The data analysis technique used Multiple Linear Regression using Eviews 12. The results stated that the gross dometic product variable partially had a negative and significant effect on velocity of money, this was indicated by the value of t count > t table, which is -4.002220 > 2.021075, while the inflation variable has no effect on velocity of money with the value of t calculate < t table, which is -0.084848 < 2.021075 and the variable interest rate has a positive effect on velocity of money with the value of t calculate > t table, which is 3.200801 > 2.021075. Simultaneously (together) gross domestic product, inflation, and interest rates have a significant effect on the velocity of money in Indonesia with f calculated > f table which is 27.04354 > 2.838745.